Plant community richness and foliar fungicides impact soil Streptomyces inhibition, resistance, and resource use phenotypes - Michalska-Smith, Matthew; Schlatter, Daniel C.; Pombubpa, Nuttapon; Castle, Sarah C.; Grandy, A. Stuart; Borer, Elizabeth T.; Seabloom, Eric W.; Kinkel, Linda L. (Frontiers in Microbiology, 2024)
Plants serve as critical links between above-and below-ground microbial communitites, both influencing and being influenced by microbes in these two realms. Below-ground microbial communities are expected to respond to soil resource environments, which are mediated by the roots of plants that can, in turn, be influenced by the above-ground community of foliar endophytes. For instance, diverse plant communities deposit more, and more diverse, nutrients into the soil, and this deposition is often increased when foliar pathogens are removed. Differences in soil resources can alter soil microbial composition and phenotypes, including inhibitory capacity, resource use, and antibiotic resistance. In this work, we consider plots differing in plant richness and application of foliar fungicide, evaluating consequences on soil resource levels and root-associated Streptomyces phenotypes. Soil carbon, nitrogen, phosphorus, potassium, and organic matter were greater in samples from polyculture than monoculture, yet this increase was surprisingly offset when foliar fungal communities were disrupted. We find that Streptomyces phenotypes varied more between richness plots-with the Streptomyces from polyculture showing lower inhibitory capacity, altered resource-use profiles, and increased antibiotic resistance-than between subplots with/without foliar fungicide. Where foliar fungicide affected phenotypes, it did so differently in polyculture than in monoculture, for instance decreasing niche width and overlap in monoculture while increasing them in polyculture. No differences in phenotype were correlated with soil nutrient levels, suggesting 1 Michalska-Smith et al.Streptomyces phenotypes respond to fungicide, plant richness the need for further research looking more closely at soil resource diversity and particular compounds that were found to differ between treatments.